Choice-relevant information transformation along a ventrodorsal axis in the medial prefrontal cortex - David J.-N. Maisson (Nature Portfolio, 2021)
Choice-relevant computations across the medial prefrontal cortex differ only quantitatively between areas. Here the authors suggest these computations may be organized along a functional gradient.